2008
DOI: 10.1093/bjsw/bcn016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Parental Drug/Alcohol Problems on Children and Parents in a Midlands County in 2005/06

Abstract: This small-scale research project used semi-structured interviews and a 'Draw and Write' technique to explore the views of parents / carers and children and young people about the impact of parental substance use and implications for services. Most adult participants had recognised their need for help and had obtained treatment for their drug / alcohol use. Children were aware of the emotional turmoil caused by their parents' substance use; social workers were important people in their lives. Families in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(83 citation statements)
references
References 15 publications
2
78
0
3
Order By: Relevance
“…Findings highlight the role of adverse personal histories of neglect, abuse, and violence that appeared to carry over from childhood into adulthood, possibly predisposing women to drug use to fulfill many needs such as escape from pain and trauma as has been found in earlier studies (Hardesty & Black, 1999). A significant proportion of participants in the current study had been mandated to treatment and, similar to earlier studies (Fraser et al, 2009), the primary motivation for treatment was the threat of their children's removal temporarily or permanently from their custody. Mothers in the current study expressed intense feelings about their bonds with their children and forcefully underscored their central identities as mothers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Findings highlight the role of adverse personal histories of neglect, abuse, and violence that appeared to carry over from childhood into adulthood, possibly predisposing women to drug use to fulfill many needs such as escape from pain and trauma as has been found in earlier studies (Hardesty & Black, 1999). A significant proportion of participants in the current study had been mandated to treatment and, similar to earlier studies (Fraser et al, 2009), the primary motivation for treatment was the threat of their children's removal temporarily or permanently from their custody. Mothers in the current study expressed intense feelings about their bonds with their children and forcefully underscored their central identities as mothers.…”
Section: Discussionsupporting
confidence: 81%
“…Findings from the current study also pointed to substance-abusing women's commitment to treatment completion and its link to child custody and parenting. Under these circumstances, substance abuse counselors and child welfare workers often serve as the key and possibly only sources of help and support as has been reported in earlier research (Fraser et al, 2009). Hence, outreach should be included as a key component of service provision not only in substance abuse treatment and child welfare programs but in community-based and medical settings as well; especially prenatal and pediatric care (Berry et al, 2003;Lam, Wechsberg, & Zule, 2004).…”
Section: Implications For Social Work Practicementioning
confidence: 84%
“…A high proportion of these families commended the contributions of specialist drug and alcohol agencies. Echoing the findings of Fraser et al (2009), some parents heavily dependant on substances were motivated to change their habits by their desire to continue or resume caring for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Haggerty et al (2008) showed that family interventions have a pivotal role in reducing the substance use disorders among the male children of drug abusers. Family intervention for the families of drug abusers may provide support and resources for the children according to the available methods for the drug abuser intervention (Fraser et al 2009;Gilchrist and Taylor 2009). Dore et al (1995) thought that it was not feasible to enact laws to punish psychoactive drug use behavior during pregnancy.…”
Section: Mental Health Of Children Of Drug Abusersmentioning
confidence: 99%